Analisis Pengaruh Penerapan Sistem Informasi Keuangan, Sistem Pengawasan Melekat Dan Prinsip Transparansi Terhadap Akuntabilitas Pengelolaan Anggaran Pendapatan Dan Belanja Daerah (APBD) (Studi Empiris Pada DPRD Kabupaten Rembang) - Rosa Nikmatul Fajri; Djumali Djumali; Sri Hartono (UMSurabaya Publishing, 2019)
ABSTRACT This study discusses the Analysis of the Effect of the Implementation of the Financial Information System, the Adherent Supervision System and the Transparency Principle on the Management of Regional Budget and Expenditure (APBD) which will be carried out in the Rembang Regional Representative Council (DPRD) Secretariat. In this study aims to determine the direction of budget realization at the Secretariat, knowing the effectiveness and efficiency of the inherent supervision system and proving that the principle of transparency is optimal in its implementation. Sources of data and data collection methods The main research needed is to use primary data, namely data sources obtained from respondents through surveys, questionnaires and purposive sampling. Data analysis using Smart Partial Least Square (SmartPLS). In this study concluded that 1) t statistics> from t table is significant at 0.05 (t statistics> t table 1.96). This means that Hypothesis 1 (H1) which states that